When shared cognition leads to closed minds: temporal mental models, team learning, adaptation and performance - Santos, C. M. (2016)
In this study we examined the moderating effect of temporal mental model accuracy on the relationship between temporal mental model similarity and team learning. Further, we investigated the mediating mechanism of team adaptation in the relationship between team learning and performance. The study was conducted in a management simulation involving 68 teams (319 individuals). We collected data at three time points. The results showed that when accuracy is high, temporal mental model similarity is not significantly related to team learning; whereas, when accuracy is low, the more similar the team members’ mental models are, the less they engage in learning behaviors. This suggests that sharing an inaccurate mental model leads to closed minds. In addition, we found team adaptation to mediate the relationship between team learning and performance. These findings emphasize the importance of temporal mental models in predicting team learning, and the importance of team learning for team adaptation and performance.